Islamisasi Ekonomi Madzhab Mainstream: Tinjauan, Model dan Implikasi - Rahmad Hakim (Iqtishodia: Jurnal Ekonomi Syariah, 2016)
The rapid development of Islamic financial institutions lately is quite encouraging, it would be legitimacy that Islam is able to renpond the challenges of globalization and modernization. On the other hand, these developments would make the Islamic financial institutions as a measure of doctrine and Islamic values realized in the lives of all Muslims. But, about Islamic products and a contract thatâ€˜s practiced is being debated by economist Muslims worldwide.Assuming that ijtihad can be done in muâ€Ÿamalat according to the rule â€œal-Aslu fi l muâ€ŸamalÄt al ibahah illa yaâ€Ÿti dalilun â€žala taÑ’rÄ«mihaâ€ make this debate more interenting with many opinions expressed by economist Muslims, especially Muslim mainstream economists.The core of the debate between Muslim economists is the method that being used in building the Islamic economic, either by adopting the practices, systems and the values of conventional economics that are relevant to shariah, or through methodology of ushÅ«l fiqh and fiqh which is purely a method derives from treasury of Islamic knowledge constructed by scientist Islam as Imam as-SyÄfiâ€˜Ä«, Imam al-GhÄzalÄ«, IzzudÄ«n Ibn SalÄm, and Imam as-SyÄtibÄ«.The focus of this paper is, first, examine approaching of some Muslim economists mainstream madzhab in the economics Islamisation. Second, examines the implications of the approach used by the Muslim economists in Islamic economic intitutions (shariah banking/Islamic banking).